2017
DOI: 10.1152/ajpregu.00039.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of face/head and whole body cooling during passive heat stress on human somatosensory processing

Abstract: We herein investigated the effects of face/head and whole body cooling during passive heat stress on human somatosensory processing recorded by somatosensory-evoked potentials (SEPs) at C4' and Fz electrodes. Fourteen healthy subjects received a median nerve stimulation at the left wrist. SEPs were recorded at normothermic baseline (Rest), when esophageal temperature had increased by ~1.2°C (heat stress: HS) during passive heating, face/head cooling during passive heating (face/head cooling: FHC), and after HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
5
2
Order By: Relevance
“…Our data suggest that ascending signals in human somatosensory processing, including subcortical and cortical levels, were delayed by decreases in body temperature. In contrast, our previous studies using SEPs revealed that the conduction velocity of the as- cending somatosensory input was accelerated by increases in body temperature (36,39,41). We also showed the delay in the latency of SEPs during whole body skin cooling after passive heat stress (41).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Our data suggest that ascending signals in human somatosensory processing, including subcortical and cortical levels, were delayed by decreases in body temperature. In contrast, our previous studies using SEPs revealed that the conduction velocity of the as- cending somatosensory input was accelerated by increases in body temperature (36,39,41). We also showed the delay in the latency of SEPs during whole body skin cooling after passive heat stress (41).…”
Section: Discussioncontrasting
confidence: 76%
“…The peak amplitude of each component was identified immediately prior (i.e., peakto-peak). Based on previous studies (33,36,40,41), we focused on the C4= and Fz electrodes. Peak latencies at C4= were identified in the P14, N20, P25, N35, P45, and N60 components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as mentioned above, to avoid the effect of sweat on the EEG paste, we reattached all electrodes just before ERP recordings in Heat and Recovery sessions. Our previous study using the same procedure as in the present study showed that the amplitudes of some components in somatosensory evoked potentials (SEPs) reduced during passive heat stress, but other components did not [22,23]. If the presence of sweat influences the SEP waveforms, all SEP components should be distorted.…”
Section: The Effect Of Task Modality and Difficulty On Eeg-erpsmentioning
confidence: 48%